Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)ab(a+b)-bc(b+c)+ac(a-c)
=ab(a+b)-bc(b+c)+ac\([\left(a+b\right)-\left(b+c\right)]\)
=ab(a+b)-bc(b+c)+ac(a+b)-ac(b+c)
=(a+b)(ab+ac)-(b+c)(bc+ac)
=(a+b)a(b+c)-(b+c)c(b+a)
=(a+b)(b+c)(a-c)
\(\left(a+b+c\right)\left(ab+bc+ca\right)-abc\)
\(=a^2b+abc+ca^2+ab^2+b^2c+abc+abc+bc^2+ac^2-abc\)
\(=a^2b+a^2c+ab^2+b^2c+c^2a+bc^2+ac^2+2abc\)
\(=\left(a^2b+ba^2+abc\right)+\left(b^2c+c^2b+abc\right)+\left(ac^2+ca^2\right)\)
\(=ab\left(a+b+c\right)+bc\left(a+b+c\right)+ac\left(a+c\right)\)
\(=\left(a+b+c\right)\left(ab+bc\right)+ac\left(a+c\right)\)
\(=b.\left(a+b+c\right)\left(a+c\right)+ac\left(a+c\right)\)
\(=\left(a+c\right)\left(ab+b^2+bc+ac\right)\)
\(=\left(a+c\right)\left[b.\left(a+b\right)+c.\left(a+b\right)\right]\)
\(=\left(a+c\right)\left(a+b\right)\left(b+c\right)\)
\(\text{(a+b+c)(ab+bc+ca)-abc=}a^2b+abc+a^2c+ab^2+b^2c+abc+abc+bc^2+ac^2-abc\)
\(=\left(a^2b+2abc+bc^2\right)+\left(a^2c+ac^2\right)+\left(ab^2+b^2c\right)\)
\(=b\left(a^2+2ac+c^2\right)+ac\left(a+c\right)+b^2\left(a+c\right)\)
\(=\left(a+c\right)\left[b\left(a+c\right)+ac+b^2\right]\)
\(=\left(a+c\right)\left(ab+bc+ac+b^2\right)\)
\(=\left(a+c\right)\left[a\left(b+c\right)+b\left(b+c\right)\right]\)
\(=\left(a+c\right)\left(a+b\right)\left(b+c\right)\)